Incorporation of purple cabbage dye on Nata de Coco - Baltero, Kris Dadivas
Cellulose has become the concept of many scientific studies because of its various functions and special characteristics. Bacterial cellulose (BC) was found to be a good source of cellulose and its utilization as a raw material in paper making was considered in this study. This study was limited in synthesizing bacterial cellulose thin film from the Acetobacter xylinum strain and solely in the presence of purple cabbage dye. The BC films were cut into strips with a dimension of 1cm x 2cm. The synthesized BC films and color chart preparted can be used only in determining pH of solutions whose pH value falls within the pH range of 2.0 to 12.0. The only test solution was phosphate buffer.